Case Report: Iatrogenic intraperitoneal hematoma compresses the ureters leading to urogenic sepsis - Zhang, Zhengyi; Ding, Peng; Yang, Meijie; Zhou, Xiujuan; Long, Kunlan (Frontiers in Medicine, 2025)
BackgroundUrogenic sepsis is a systemic inflammatory response syndrome triggered by infections of the genitourinary tract. It is characterized by complex etiology, atypical clinical symptoms, rapid disease progression, and difficulty in treatment, making it a focal point and challenge in clinical diagnosis and therapy. Although endovascular interventions are effective in treating conditions such as iliac artery thrombosis, they can also lead to complications such as arterial rupture and subsequent hematoma formation. This article reports a rare case of urogenic sepsis that developed secondary to urinary tract obstruction and infection caused by compression of the ureter due to an iatrogenic retroperitoneal hematoma following endovascular surgery.Case introductionA 63-year-old male patient was admitted to the hospital with symptoms of severe viral pneumonia and acute heart failure. Two months earlier, the patient had undergone a vascular interventional procedure, during which a rupture of the left iliac artery led to the formation of an intra-abdominal hematoma, a condition that was not given due attention at the time. Although initial treatment was provided for the respiratory and cardiac issues, the patient’s condition continued to deteriorate. Subsequent examinations revealed that the hematoma was compressing the ureters, causing severe ureteral obstruction and urinary sepsis. The patient then underwent an emergency transurethral ureteral stent implantation. Following the procedure, the patient’s condition significantly improved, and he was eventually discharged from the hospital.ConclusionCases of iatrogenic intraperitoneal hematoma compressing the ureters and subsequently causing urogenic sepsis are extremely rare in clinical practice. This case highlights the necessity of early identification and intervention of iatrogenic complications, especially in the patient population with a history of vascular interventional surgery. It underscores the crucial role of targeted diagnostic strategies and surgical interventions in resolving the challenge of mechanical obstruction. The research findings indicate that it is essential to establish a multidisciplinary collaborative mechanism to effectively manage such complex cases.